A binary logistic regression analysis of factors influencing repeat purchase for snack product x - Maharani, Oci Citra (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aimed to analyze the factors influencing repeat purchase of product X, a popular snack product in Indonesia, using binary logistic regression. Data were collected through an internal questionnaire distributed to 100 respondents and analyzed using SPSS. The results showed that among demographic variables, social media usage, product perception, and the influence of TV advertising, only the TV advertising variable had a significant effect on repeat purchase. Respondents exposed to TV advertising were 3.877 times more likely to make a repeat purchase. The resulting binary logistic regression model had a prediction accuracy of 77.2%. However, the prediction accuracy for non-repeat purchase was still low (8%), indicating the presence of other unidentified factors. It is recommended that the marketing team of company X conduct research on TV advertising concepts that are in line with the target market, implement a marketing mix between TV channels and social media, explore alternative media channels to support TV advertising, and maintain product quality and brand image.